Malignant Hyperthermia - Fajri, Doni; Hidayat, Nopian; Masjkur, Diana (JAI (Jurnal Anestesiologi Indonesia), 2025)
Malignant hyperthermia (MH) is a life-threatening clinical syndrome caused by hypermetabolism involving skeletal muscle. MH is very rare, but it is one of the causes of death in the operating room. MH is an autosomal dominant disease and can be triggered when exposed to certain anesthetic drugs. Genetic tests can help diagnose, but the gold standard is the caffeine halothane contracture test (CHCT). Initial symptoms are a decrease in pH and oxygen, as well as an increase in CO2, lactate, potassium, and temperature. The increase in lactate reflects tissue hypoxia. Dantrolene is an antidote to MH, by reducing calcium loss from the sarcoplasmic reticulum in skeletal muscle and returning metabolism to normal conditions. Immediate detection and treatment can improve MH outcomes.